Peningkatan Efisiensi Layanan di Industri Kreatif Melalui Integrasi Lean Six Sigma dan SERVQUAL: Studi Kasus pada Agensi Kreatif XYZ - Ardadi, Bonifasius Bima Sakti; Aritonang, Y.M. Kinley (Universitas Katolik Parahyangan, 2025)
This study discusses the urgency of improving operational efficiency and service quality in the creative industry by addressing theoretical gaps in the application of Lean Six Sigma (LSS) and SERVQUAL methodologies. XYZ Creative Agency, a provider of social media management services, was selected as a case study to emphasize the practical contributions of the research. The main challenges include service delivery delays and insufficient service assurance. The Lean Six Sigma and SERVQUAL methods were applied to analyze and resolve these issues. The SERVQUAL analysis results revealed positive gaps in the assurance dimension (+0.0615) and the reliability dimension (+0.0154), indicating the need to enhance information clarity, client trust, and service timeliness. Value Stream Mapping (VSM) identified that delays primarily occurred during the content approval stage, while Fishbone Diagram analysis uncovered root causes such as inadequate team coordination, ineffective communication, and underutilized technology. Implemented solutions included the use of a digital project management platform to improve process transparency and efficiency, regular employee training to enhance competencies, and the development of a client feedback system. The DMAIC approach employed in Lean Six Sigma proved effective in designing data-driven solutions to improve operational efficiency and service quality. The implementation of these solutions is expected to reduce delays, enhance client satisfaction, and strengthen XYZ’s competitiveness in the creative industry.